Comparative Study of the Effects of Fluconazole and Voriconazole on Candida glabrata, Candida parapsilosis and Candida rugosa Biofilms - Madhavan, Priya; Jamal, Farida; Pei, Chong Pei; Othman, Fauziah; Karunanidhi, Arunkumar; Ng, Kee Peng (Springer Verlag, 2018)
Infections by non-albicans Candida species are a life-threatening condition, and formation of biofilms can lead to treatment failure in a clinical setting. This study was aimed to demonstrate the in vitro antibiofilm activity of fluconazole (FLU) and voriconazole (VOR) against C. glabrata, C. parapsilosis and C. rugosa with diverse antifungal susceptibilities to FLU and VOR. The antibiofilm activities of FLU and VOR in the form of suspension as well as pre-coatings were assessed by XTT [2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide] reduction assay. Morphological and intracellular changes exerted by the antifungal drugs on Candida cells were examined by scanning electron microscope (SEM) and transmission electron microscope (TEM). The results of the antibiofilm activities showed that FLU drug suspension was capable of killing C. parapsilosis and C. rugosa at minimum inhibitory concentrations (MICs) of 4× MIC FLU and 256× MIC FLU, respectively. While VOR MICs ranging from 2× to 32× were capable of killing the biofilms of all Candida spp tested. The antibiofilm activities of pre-coated FLU were able to kill the biofilms at ¼× MIC FLU and ½× MIC FLU for C. parapsilosis and C. rugosa strains, respectively. While pre-coated VOR was able to kill the biofilms, all three Candida sp at ½× MIC VOR. SEM and TEM examinations showed that FLU and VOR treatments exerted significant impact on Candida cell with various degrees of morphological changes. In conclusion, a fourfold reduction in MIC50 of FLU and VOR towards ATCC strains of C. glabrata, C. rugosa and C. rugosa clinical strain was observed in this study.